The STAP-study: The (cost) effectiveness of custom made orthotic insoles in the treatment for plantar fasciopathy in general practice and sports medicine: design of a randomized controlled trial. Issue 1 (December 2016) - Rasenberg, N.; Fuit, L.; Poppe, E.; Kruijsen-Terpstra, A.; Gorter, K.; Rathleff, M.; van Veldhoven, P.; Bindels, P.; Bierma-Zeinstra, S.; van Middelkoop, M.
Abstract Background Plantar fasciopathy is a common cause of foot pain, accounting for 11 to 15 % of all foot symptoms requiring professional care in adults. Although many patients have complete resolution of symptoms within 12 months, many patients wish to reduce this period as much as possible. Orthotic devices are a frequently applied option of treatment in daily practice, despite a lack of evidence on the effectiveness. Therefore, the objective is to study the (cost)-effectiveness of custom made insoles by a podiatrist, compared to placebo insoles and usual care in patients with plantar fasciopathy in general practice and sports medicine clinics. Method/design This study is a multi-center three-armed participant and assessor-blinded randomized controlled trial with 6-months follow-up. Patients with plantar fasciopathy, with a minimum duration of complaints of 2 weeks and aged between 18 and 65, who visit their general practitioner or sport physician are eligible for inclusion. A total of 185 patients will be randomized into three parallel groups. One group will receive usual care by the general practitioner or sports physician alone, one group will be referred to a podiatrist and will receive a custom made insole, and one group will be referred to a podiatrist and will receive a placebo insole. The primary outcome will be the change from baseline to 12 weeks follow-up in pain severity at rest and during activity on a 0–10 numerical rating scale (NRS). Secondary outcomes include foot function (according to the Foot Function Index) at 6, 12 and 26 weeks, recovery (7-point Likert) at 6, 12 and 26 weeks, pain at rest and during activity (NRS) at 6 and 26 weeks and cost-effectiveness of the intervention at 26-weeks. Measurements will take place at baseline and at, 2, 4, 6, 12 and 26 weeks of follow-up. Discussion The treatment of plantar fasciopathy is a challenge for health care professionals. Orthotic devices are frequently applied, despite a lack of evidence of the effectiveness on patient reported outcome. The results of this randomized controlled trial will improve the evidence base for treating this troublesome condition in daily practice. Trial registration Dutch Trial Registration:NTR5346 . Date of registration: August 5th 2015.